The Rule of Work Environment and Discipline on the Performance of Bank Muamalat Employees in Sorong City - Damanik, Lisa Gresti Sella; Edwar, Rizka Cintya; Landjang, Xenia Irene Sandy; Mangopo, Yuni Riskita (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2024)
This study aims to analyze the influence of work environment and work discipline on improving the performance of Muamalat Bank employees throughout Sorong City. The method used in this study is a quantitative method. The number of samples used was 36 Muamalat Bank employees throughout Sorong City. The 36 respondents are permanent employees from Bank Muamalat and the reason the author used a sample of permanent employees is because they tend to have a higher commitment to the organization because they have invested time and energy in the long term. The data collection technique was by distributing and distributing questionnaires to predetermined samples. Furthermore, it was processed using the SPSS (Statistical Program for Social Science) analysis technique. The results of this study indicate that (1) the work environment has a positive and significant effect on the performance of Muamalat Bank employees throughout Sorong City, (2) work discipline has a negative and insignificant effect on the performance of Muamalat Bank employees throughout Sorong City. So it can be concluded that hypothesis 1 can be accepted while hypothesis 2 is not accepted.